Rebuilding from the vacuum: A qualitative study of people with a recent history of incarceration - Fachilla, Frances E. (Journal of addictions & offender counseling, 2023)
Thirty-four adults recently released from incarceration and living in transitional homes were interviewed in this qualitative study. An open-ended approach to interviewing was used to allow participants’ main concerns to emerge. Participants were primarily focused on rebuilding relationships to achieve stability post-incarceration. Participants who rebuilt stable relationships were able to work on internal goals (e.g., sobriety). Participants who did not rebuild stable relationships returned to existing social networks of unstable connections characterized by drug addiction, abuse, or criminal activity.